ANALYSIS OF BUSINESS MODELS - A., Prodanova N.; A., Askarova Zh.; S., Kyzdarbekova A. (Farabi Journal of Social Sciences, 2020)
The term “business model” has been used in practice for several years, but companies create, define and implement their models subconsciously from the very beginning of the business. The article discusses the concept of a business model and the main approaches to its understanding. A systematic presentation and analysis of the business model of the enterprise, the influence of classifiers on the implementation of the life of the company. It is shown that the analysis of the relationships between the main elements of the business model allows us to identify problems of co mpliance and sustainability of the business model. The most general scheme for a systematic description of a business model can be its representation through system elements. The value of the study lies in the fact that a model for the use of a business model is defined. The practical significance of the study is to create an analytical tool and analysis of a real business model, and the characteristics of each part of the business model, that is, customers, distribution, cost, resources, activities, costs and revenues are determined. The value chain is one of the central concepts of strategic management, which was first presented in the works of M. Porter. As you know, the value for the consumer is created in the company as a result of two types of activities (main and auxiliary). The conclusion discusses the most commonly used characteristics, extremes, inconsistencies and the most important facts that were found in the study.